2022
DOI: 10.1097/spv.0000000000001251
|View full text |Cite
|
Sign up to set email alerts
|

Examining Age and Postoperative Opioid Use in the Urogynecology Population: A Prospective Study

Abstract: Importance Surgeons must individualize postoperative pain management while also reducing the amount of unused prescribed opioids. Objectives This study compared postoperative opioid use in younger versus older women following urogynecologic surgery. We also assessed the likelihood of women returning unused opioids for safe disposal. Study Design This was a prospective study of women undergoing pelvic reconst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Prior studies have suggested an association between younger age and increased pain or opioid following pelvic reconstructive surgery, specifically in a POP population. 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 Notably, many of these studies dichotomized age at different and arbitrary cut‐points, resulting in a loss of statistical efficiency and inability to characterize opioid use fully across the spectrum of patient ages (such as exploring for the presence of a parabola or plateau effect). 12 , 13 , 14 , 15 , 16 , 17 , 19 , 24 For example, Willis‐Gray (2019) analyzed 183 US patients who underwent POP or stress incontinence surgery and reported that women aged 65 and younger were more likely to be given opioids and received higher amounts of opioids while in post‐anesthesia care than were women older than 65 years, after controlling for surgical factors, depression and body mass index.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies have suggested an association between younger age and increased pain or opioid following pelvic reconstructive surgery, specifically in a POP population. 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 Notably, many of these studies dichotomized age at different and arbitrary cut‐points, resulting in a loss of statistical efficiency and inability to characterize opioid use fully across the spectrum of patient ages (such as exploring for the presence of a parabola or plateau effect). 12 , 13 , 14 , 15 , 16 , 17 , 19 , 24 For example, Willis‐Gray (2019) analyzed 183 US patients who underwent POP or stress incontinence surgery and reported that women aged 65 and younger were more likely to be given opioids and received higher amounts of opioids while in post‐anesthesia care than were women older than 65 years, after controlling for surgical factors, depression and body mass index.…”
Section: Discussionmentioning
confidence: 99%
“… 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 Notably, many of these studies dichotomized age at different and arbitrary cut‐points, resulting in a loss of statistical efficiency and inability to characterize opioid use fully across the spectrum of patient ages (such as exploring for the presence of a parabola or plateau effect). 12 , 13 , 14 , 15 , 16 , 17 , 19 , 24 For example, Willis‐Gray (2019) analyzed 183 US patients who underwent POP or stress incontinence surgery and reported that women aged 65 and younger were more likely to be given opioids and received higher amounts of opioids while in post‐anesthesia care than were women older than 65 years, after controlling for surgical factors, depression and body mass index. Additionally, potential confounding due to preoperative pain and patient factors, such as mental health, known to be related to patient age and associated with postoperative pain and opioid use, has been incompletely accounted for to date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation